Un-Speaking in Tongues: Glossolalia as Ascetical Prayer. Issue 1 (May 2020) - Stephenson, Christopher A.
One of the next steps of integrating Pentecostal spirituality with the wider Christian spiritual tradition is to consider further glossolalia's relationship to forms of prayer with a longer and more firmly established history. While some initial attempts to do so have connected glossolalia more closely to mystical prayer, there is ground for seeing some occasions of glossolalia also as ascetical prayer. Pentecostals and Catholics are particularly equipped to support this claim, if they can transcend some of their own typical views of glossolalia and accentuate other tendencies within their own traditions. The result may be a clearer understanding of glossolalia for all interested parties, an understanding marked by new insights about glossolalia's value as an unintelligible form of prayer that is widely available for regular use.